2016
DOI: 10.1111/anec.12401
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypocalcemia mimicking ST-segment elevation acute myocardial infarction

Abstract: Hypocalcemia is mainly the consequence of hypoalbuminemia, advanced renal impairment, cirrhosis, malnutrition, or sepsis. The most common ECG manifestation of hypocalcemia is QT prolongation as a result of ST segment lengthening. Very occasionally, hypocalcemia can manifest with ST segment elevation forcing the differential diagnosis with ST elevation MI. We described a case of severe hypocalcemia manifesting in electrocardiogram with a J point elevation, absent of ST segment and with associated short QT inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…As it is known, the duration of the ST segment is inversely proportional to the plasmatic calcium concentration [ 3 ]. Consistent with that, corrected QT interval was prolonged in most of the patients, except for the one described by Kukla et al [ 4 ], who presented with a shortened QT. Authors suggested the hypothesis of a coronary artery spasm as a possible cause.…”
supporting
confidence: 84%
“…As it is known, the duration of the ST segment is inversely proportional to the plasmatic calcium concentration [ 3 ]. Consistent with that, corrected QT interval was prolonged in most of the patients, except for the one described by Kukla et al [ 4 ], who presented with a shortened QT. Authors suggested the hypothesis of a coronary artery spasm as a possible cause.…”
supporting
confidence: 84%
“…22 La traducción electrocardiográfica más común de hipocalcemia es la prolongación del intervalo QT (Figura 5) como resultado del alargamiento del segmento ST, ocasionalmente, la hipocalcemia puede manifestarse con elevación del segmento ST, simulando un evento isquémico a nivel miocárdico. 23 Hipomagnesemia. El magnesio es un componente esencial de las estructuras del ácido desoxirribonucleico (ADN) y ácido ribonucleico (ARN) a nivel celular.…”
Section: )unclassified
“…Although it is uncommon, hypocalcemia can cause ST-segment elevation [75]. After searching the PubMed and Google Scholar databases for hypocalcemia mimicking acute STEMI, many cases were found [75][76][77][78][79].…”
Section: Hypocalcemiamentioning
confidence: 99%